BEFTIGRE: Behaviour‐driven full‐tier green evaluation of mobile cloud applications. Issue 2 (28th January 2017) - Chinenyeze, Samuel J.; Liu, Xiaodong; Al‐Dubai, Ahmed
Abstract: With the resource‐constrained nature of mobile devices and the resource‐abundant offerings of the cloud, several promising optimisation techniques have been proposed by the green computing research community. Prominent techniques and unique methods have been developed to offload resource intensive tasks from mobile devices to the cloud. Although these schemes address similar questions within the same domain of mobile cloud application (MCA) optimisation, evaluation is tailored to the scheme and also solely mobile focused, thus making it difficult to clearly compare with other existing counterparts. In this work, we first analyse the existing/commonly adopted evaluation technique, then with the aim to fill the above gap, we propose the behaviour‐driven full‐tier green evaluation approach, which adopts the behaviour‐driven concept for evaluating MCA performance and energy usage—ie, green metrics. To automate the evaluation process, we also present and evaluate the effectiveness of a resultant application program interface and tool driven by the behaviour‐driven full‐tier green evaluation approach. The application program interface is based on Android and has been validated with Elastic Compute Cloud instance. Experiments show that Beftigre is capable of providing a more distinctive, comparable, and reliable green test results for MCAs. Abstract : This article presents a novel approach to evaluate offloading of resource‐intensive tasks in mobile cloud applications. The novelty of the approach mainly consists in integrating BDD and in making a full‐tier analysis. Full tier in this case means that not only the local (mobile) impact of offloading is evaluated but also the server‐side (cloud) impact. The aim is to evaluate offloading techniques in their impact on the system as a whole.